UV‐CD12: synchrotron radiation circular dichroism beamline at ANKA. (10th April 2015) - Bürck, Jochen; Roth, Siegmar; Windisch, Dirk; Wadhwani, Parvesh; Moss, David; Ulrich, Anne S.
<x xml:space="preserve">Abstract</x> Synchrotron radiation circular dichroism (SRCD) is a rapidly growing technique for structure analysis of proteins and other chiral biomaterials. UV‐CD12 is a high‐flux SRCD beamline installed at the ANKA synchrotron, to which it had been transferred after the closure of the SRS Daresbury. The beamline covers an extended vacuum‐UV to near‐UV spectral range and has been open for users since October 2011. The current end‐station allows for temperature‐controlled steady‐state SRCD spectroscopy, including routine automated thermal scans of microlitre volumes of water‐soluble proteins down to 170 nm. It offers an excellent signal‐to‐noise ratio over the whole accessible spectral range. The technique of oriented circular dichroism (OCD) was recently implemented for determining the membrane alignment of α‐helical peptides and proteins in macroscopically oriented lipid bilayers as mimics of cellular membranes. It offers improved spectral quality <200 nm compared with an OCD setup adapted to a bench‐top instrument, and accelerated data collection by a factor of ∼3. In addition, it permits investigations of low hydrated protein films down to 130 nm using a rotatable sample cell that avoids linear dichroism artifacts.